ANTAGONISTIC KINDNESS IN CHARLOTTE PERKINS GILMAN’S “THE YELLOW WALLPAPER” - Saadah, Sufi Ikrima; Setyawan, Mochamad Andry; Prabowo, Alvandi Rizki; Ismahendra, Galih (UIN Alauddin Makassar, 2022)
This article depicts John’s attitude in treating his wife’s nervous depression in Charlotte Perkins Gilman’s “The Yellow Wallpaper.” The treatment is supposed to help the wife get better. Yet, she ends up with a severe mental breakdown. The researchers argue that John’s attitude towards his sickly wife is what is called antagonistic kindness. This study employed the qualitative descriptive method through the perspective of feminist literary criticism. Since the narrator is the wife, the data were taken from the wife’s accounts of John’s acts and speeches towards her during the special treatment in the rented mansion. The wife’s thoughts on John also serve as the essential data to show how manipulative and dictating John is. The research indicates that John’s attitude embodies antagonistic kindness manifested in two major cruel-kindness actions or decisions, including psychological manipulation and dictation towards his wife. John keeps saying that all the treatment is for the wife’s sake, yet, he says such a thing to make the wife feel guilty for being a burden. Moreover, John has his wife’s daily activities scheduled, preventing her from doing anything out of his control. He never listens to what his wife wants or feels, thus worsening the wife’s psychological condition. The researchers further argue that John exhibits the so-called antagonistic kindness to maintain his reputation as a physician of high standing and keep dominating his wife as his property. The findings thus might help the readers be aware of any forms of kindness that antagonize and manipulate them psychologically.